Sonographic features of pelvic pain among adults in a Nigerian population - Eze, Joseph C.; Ezugwu, Emmanuel E.; Nwodo, Victor K.; Ugwuanyi, Daniel C.; Ezeh, James E. (International Journal of Advances in Medicine, 2022)
Background: Pelvic pain is abdominal pain located below the level of umbilicus, including frequent lower back pain with or without radiation to the thighs. The aim of this study was to evaluate the common ultrasound findings in subjects with pelvic pain. Methods: It was a retrospective study and involved collection of information from the folders of the subjects. A total of 820 folders were used for this study. Information collected from these folders included; the age, sex, provisional diagnosis and ultrasound findings. Data collected was arranged and statistical package for social sciences (SPSS) version 20 was used for analysis. Descriptive statistics was used and results arranged in frequency tables and percentages. Results: The result showed that males were 160 (20%) and females were 660 (80%). The age ranged from < 20years to 70 years and above. The mean age of the subjects was 35.66±15.82 years. The mean age of the male is 51.83±21.56 years and that of the females is 31.77±11.02 years. Normal scan was the predominant ultrasound finding. The most common pathological finding was uterine fibroid (21.3%) and followed by pelvic inflammatory disease (15.2%). Conclusions: Ultrasound is an essential tool in the diagnosis of pelvic pain in males and females. Uterine fibroid was the most common pathological finding in females while benign prostate hypertrophy was the most common in males.